Association between the pharmacokinetics of capecitabine and the plasma dihydrouracil to uracil ratio in rat: A surrogate biomarker for dihydropyrimidine dehydrogenase activity. (21st January 2019) - Kobuchi, Shinji; Akutagawa, Mako; Ito, Yukako; Sakaeda, Toshiyuki
Abstract: Capecitabine is a 5‐fluorouracil (5‐FU) derivative that is used widely in the treatment of colorectal cancer. The plasma ratio of dihydrouracil (UH2 ) to uracil (Ura) is expected to gain relevance as an indirect‐response biomarker to estimate the activity of dihydropyrimidine dehydrogenase (DPD). The latter is a rate‐limiting enzyme in the catabolism of 5‐FU in the capecitabine‐based regimen. However, the relationship between the pharmacokinetics of capecitabine and the plasma UH2 /Ura ratio is still unknown. This study evaluated the time‐course alterations of the plasma UH2 /Ura ratio in rats treated with 180 mg/kg capecitabine. The molar ratio tended to increase within 1.5 h (1.85 ± 0.76 at 1.5 h after administration of capecitabine) and gradually recovered to its initial level (1.00 ± 0.46). The results of the current study suggest that the plasma UH2 /Ura ratio temporarily increases following administration of capecitabine, possibly related to the DPD activity levels. The plasma UH2 /Ura ratio might assist in monitoring the alteration of DPD activity levels in capecitabine treatments.